OWNERSHIP STRUCTURES AND DEBT POLICY (A META-ANALYSIS) - Christian Timotius Peilouw; Bintang Kusucahyo (Jurnal Riset Akuntansi, 2022)
This study aims to understand the effect of ownership structure on debt policy, as well as to examine and analyze the variation of result study on debt policy in Indonesia. Agency Theory is the grand theory used to explain the effect of ownership structure on debt policy. This study used meta-analysis approach with sample is 31 researches in Indonesia, both the published and unpublished in 2006-2019. The result of this study, meta-analysis strengthen the findings of the previous study which stated that the ownership structure can decrease debt policy. The differences of the previous studies are due to the presence of moderation effect from the measurement model of debt policy and ownership structure.